Alternative simple method to realize p-type BaSi2 thin films for Si heterojunction solar cell applications. (13th February 2018) - Takahashi, Kazuma; Nakagawa, Yoshihiko; Hara, Kosuke O.; Takahashi, Isao; Kurokawa, Yasuyoshi; Usami, Noritaka
Abstract: A novel preparation method of B-doped p-type BaSi2 (p-BaSi2 ) is proposed to realize heterojunction crystalline Si solar cells with p-BaSi2 . The method consists of thermal evaporation of BaSi2 on B-doped amorphous Si (a-Si). In this study, the effect of a-Si interlayers and substrate temperature during BaSi2 evaporation on the electrical characteristics and crystalline quality of the evaporated films were investigated. While no cracks were found in the BaSi2 films formed using hydrogenated a-Si deposited by plasma enhanced chemical vapor deposition (PECVD), the films formed with sputtered a-Si have cracks. In addition, BaSi2 films formed with a 600 °C substrate temperature using PECVD a-Si showed p-type characteristics. After a post-deposition anneal at 800 °C for 5 minutes, the film hole density was measured at 1.3×10 19 cm -3 and boron was found to be uniformly distributed throughout the film. These results show that the proposed method using PECVD is promising to obtain p-BaSi2 thin films with high hole density for p-BaSi2 /n-type crystalline Si heterojunction solar cells.